The Cosmos and Theological Reflection: The Priority of Self-Transcendence - Allen, Paul (Théologiques, 2001)
ABSTRACTIn this article, I argue that the primary significance of cosmology for theology is through a notion of self-transcendence. It is an inherently theological notion arising within cosmology. It points to the realm of interiority claimed by contemporary theology. Employing the thought of Ernan McMullin in particular, I claim that self-transcendence emerges within cosmological inquiry when it becomes philosophy, and when extrapolation is involved. A theological thrust to cosmology is confirmed when one understands the limits of cosmology as an empirical discipline amidst the existential questions that can be posed about the meaning of the universe, a development well illustrated by the anthropic principle.